A physics based distributed integrated hydrological model in prediction of water balance of a semi-arid catchment in India. (May 2020) - Loliyana, V.D.; Patel, P.L.
Abstract: A physics based distributed coupled integrated hydrological model, MIKE SHE/MIKE 11, has been calibrated using a multi-objective optimization approach for minimization of errors in prediction of stream flows and groundwater levels within a semi-arid Yerli sub-catchment of Upper Tapi basin in India. The performance of the calibrated model has been found to improve significantly in prediction of stream flows and groundwater levels within the sub-catchment while incorporating distributed Manning's roughness coefficient, vegetation, soil and geologic parameters in the model. Also, the model has been able to simulate the soil moisture satisfactorily for the areas falling within the plain area of the sub-catchment. Analyses of water balance (period 1991–1998, 1999–2004, 2005–2009 and 2010–2012) revealed that developed integrated hydrological model could simulate better dynamics of hydrological processes in terms of change in land use, groundwater draft and irrigation practices to maximize stakeholder sustainability. Graphical abstract: Image 1 Highlights: Integrated distributed physics based hydrological modelling approach for a large semi-arid Yerli sub-catchment, India. Calibration using multi-objectives optimization approach and multi-sites validation. Prediction of stream flow, soil moisture and groundwater levels within the study area. Assessment of hydrological processes for understanding total water balance within the sub-catchment.